The normal and pathological language - Espejo, Luis D. (1919)
The extraordinary development of normal and pathological psychology has achieved in recent decades, thanks to the dual method of objective observation and oral survey enabled the researcher spirit of neuro-psychiatrist penetrate the intimate mechanism of the nervous system whose supreme manifestation is thought. It is normal psychology explaining the complicated game of perceptions: their methods of transmission, their centers of projection, its transformations and its synthesis to construct the representation of the outside world, the source of all knowledge; psychopathology and is dissociated psychic functions, clarifying the mechanism of the normal processes, revealing the infinite world of the subconscious, the warp of the normal and abnormal dreams, mental state of neurosis or language training.